An analytic study of 200 cases of head injuries admitted to teaching Hospital in Najaf. - AI Obaidi, Safa M.; Yousif, Hassan Hadi; Al-Shalchy, Ali (Journal of the Faculty of Medicine Baghdad, 2007)
Back ground: This is a prospective study of Head injury in Najaf. Aim: to study the causes & out come & way of transferring the rat to the hospital & best way to investigate them. Patients & methods:A prospective analytical study of 200 cases of Head injury patients, who were admitted to Saddam Teaching Hospital , in Najaf between 18 t" of November 1996 and 1st of September 1998. Results: All age groups were included in this study, male to female ratio was 4:1 and the highest incidence was seen at the age group below 14 years. The two most common causes of head injury were road traffic accident (RTA)(51 %) and assault (22%),of RTA pedestrians accounted for (87.25%). RTA accounted of (80%) in those with severe head injury. The highest incidence of head injuries in both male and female was between 2pm and 6pm. All patients brought to hospital by personal means, most of them reached the hospital within the first hour of injury. 115 patients (57.5%) were minor head injuries Glasgow coma scale (11-15). Skull x-ray was taken for 185 patients, it was positive for fracture in 48 patients (24%) and negative in 137 (68.5%). There is significant number of patients with negative skull X-ray who need not to be Xrayed. The commonest associated injuries were limb fractures 35% followed by injuries of abdominal viscera 11%. The incidence of operative treatment (10%). The final outcome on discharge was complete recovery in 156 patients (78%) residual neurological deficits in 18 patients (9%), and death in 20 patients (10%), and 6 patients discharged against medical advice. The common cause of head injuries in those who died was RTA 85%& we give recommendation regarding traffic roads & culture of society & policy of investigation.